Stress analysis of welded ellipsoidal end-to-shell joint of a stainless steel tank - Jusoh, Muhamad Anuwar (2011)
Welding is most widely used in metal joining. In Tungsten Inert Gas (TIG), defining the process and appropriate values for process is essential in order to control heat-affected zone (HAZ) and get the required effect of residual stress. In this investigation, metallurgical study was carried out on the heat affected zone of weld metal region for SS304 steel joint. Thermal-mechanical analysis was investigated by using finite element (FE) method. Results show that the HAZ has smaller grain size than the base metal and weld metal. FE simulation was performed using uncoupled temperature-displacement analysis with axisymmetric ellipsoidal head-to-shell of welded joint. From the analysis, the distribution of deformation is higher at the weld metal region of axisymmetric model due to the effect of different coefficient of thermal expansion (CTE) between base and weld metal. Subsequently, the distribution of residual stress is localized at the welded zone and Von Mises stress is 558.5MPa at weld metal compared to the grip area, HAZ and base metal. The distribution of equivalent plastic strain shows strains concentration at the toe of weld where the geometrical stress concentration is occurs. However, the highest impact of plastic strain is at the grip holder due to effect of constraints to hold the welded plate during the welding process.